Assessing the consequences of natural disasters on production networks: A disaggregated approach - Stéphane Hallegatte; Fanny Henriet (Fondazione Eni Enrico Mattei (FEEM), 2008)
This article proposes a framework to investigate the consequences of natural disasters. This framework is based on the disaggregation of Input-Output tables at the business level, through the representation of the regional economy as a network of production units. This framework accounts for (i) limits in business production capacity; (ii) forward propagations through input shortages; and (iii) backward propagations through decreases in demand. Adaptive behaviors are included, with the possibility for businesses to replace failed suppliers, entailing changes in the network structure. This framework suggests that disaster costs depend on the heterogeneity of losses and on the structure of the affected economic network. The model reproduces economic collapse, suggesting that it may help understand the difference between limited-consequence disasters and disasters leading to systemic failure.
Keywords: D20; Q54; R15; 330; Natural Disasters; Economic Impacts; Economic Network